Cross-cultural design. 7th International Conference, CCD 2015, held as part of HCI International 2015, Los Angeles, CA, USA, August 2-7, 2015, Proceedings /: 7th International Conference, CCD 2015, held as part of HCI International 2015, Los Angeles, CA, USA, August 2-7, 2015, Proceedings. Methods, practice and impact : Part I, (2015) - Unknown
No abstract available